Biological Cycling of Mineral Nutrients in a Temperate Forested Shale Catchment. Issue 10 (8th October 2018) - Soper, Fiona M.; Chamberlain, Samuel D.; Crumsey, Jasmine M.; Gregor, Sonia; Derry, Louis A.; Sparks, Jed P.
Abstract: Biological pumping of mineral elements (root uptake from the soil and concentration at the surface via litterfall) may be an important mechanism influencing their loss from terrestrial ecosystems by accelerating transport in runoff, though few estimates exist to assess this. In the Susquehanna Shale Hills Critical Zone Observatory (a temperate forested watershed in central Pennsylvania), we compared two independent methods (litterfall‐based and transpiration flow‐based) for estimating the total uptake of elements (Ca, K, Mg, Mn, Si, Sr, and Al) by canopy trees. Elemental concentrations were measured monthly in leaf tissue and xylem sap of dominant species Quercus rubra (chestnut oak), Q. prinus (red oak), and Acer saccharum (sugar maple) for two growing seasons. Species‐specific litterfall and transpiration (estimated by eddy covariance) were used to scale concentrations to annual fluxes. For most elements, both methods generated comparable gross fluxes in the range of 53–85 (Ca), 9–19 (Mg), 14–28 (Mn), 0.2–0.6 (Al), and 0.1–0.3 (Sr) kg·ha −1 ·year −1 . For K, litterfall‐based methods generated substantially lower estimates than transpiration, though neither accounted comprehensively for leaching from live foliage, resorption, or potential recycling within the growing season. For most elements, uptake rates were similar in magnitude to stream losses, implying a low degree of recycling. For K and Mn however, biological uptake exceeded losses by 1–2 orders of magnitude, suggesting a biological role in ecosystem retention. We conclude that litter‐ and transpiration‐based methods can be combined to broadly estimate the magnitude of biological pumping, with additional measures of wood‐/root‐based turnover necessary for more accurate budgets. Plain Language Summary: Elements such as silicon and calcium that are weathered from rocks can be moved from deep in the soil to the surface through uptake by plant roots and subsequent litterfall. At the surface, these elements are more vulnerable to being lost from an ecosystem by being eroded or washed into waterways, where they can eventually influence downstream processes such as ocean carbon uptake. It is difficult to estimate how important transport by trees is for element loss (or for recycling within the ecosystem) without good measurement methods. Here we compared two methods for estimating tree uptake of seven elements by measuring their concentrations in either leaf litter or plant sap. We measured three dominant tree species (oaks and maples) in a temperate forest catchment in central Pennsylvania and used total litterfall and sap flow to scale these concentrations into annual uptake rates. For most elements, both methods generated similar estimates that showed that the amount taken up by trees was similar to the amount lost in streams every year. However, for potassium and manganese, tree uptake was much greater than stream loss, suggesting that incorporation into tree litter helps to retain these elements within the ecosystem. Key Points: Uptake of mineral elements by trees may be a major pathway of redistribution, affecting hydrologic loss and soil formation We compared a novel transpiration‐based method with a litterfall‐based approach to estimate watershed‐scale uptake fluxes For most elements (excluding K), methods generated similar fluxes, and biological uptake was of comparable magnitude to hydrologic losses